Classical Islamic Historiography in Early Moslem and Orientalist Historiographical Works - Nurul Hak (Sunan Kalijaga: International Journal of Islamic Civilization, 2020)
The present paper elaborates some problems of classical Islamic historiography found in early and modern Islamic historiographical works. I found three problems concerning the historiography, i.e., epistemology, contents and methodology. This is an attempt to reconstruct the said problems by presenting some responses from various perspectives. The result of this study shows that the problems of classical Islamic historiography could be classified into three categories: Political history of classical Islamic historiography was mainly caused by historian biases through their interpretation to the historiography. Methodology of transmission of the prophet tradition employed by the early Moslem historians has not explained the problems yet. Last but not least, the problems must be comprehensively approached by applying a holistic perspective.